DAMPAK PROGRAM BANTUAN DALAM MENINGKATKAN KESEJAHTERAAN DESA CISERO - Fitri Khoerunisa; Ansori Ansori; Novi Widiastuti (Comm-Edu (Community Education Journal), 2023)
This study aims to determine (1) the level of community welfare, (2) the impact of social assistance programs in improving community welfare. The research assumption put forward is that researchers realize that social assistance can improve people's welfare, but there is a lack of effectiveness in distributing this assistance, such as the existence of people who do not get their rights. The theoretical basis used is the concept of welfare, the concept of social assistance, the concept of society, the concept of society, the concept of poverty. Data collection techniques used were (1) questionnaires, (2) interviews, (3) documentation. The results of the study show the positive impact of social assistance programs in improving people's welfare by providing social protection and easing the life burden of families affected by Covid-19. The negative impact is educating a lazy life, and prone to conflict.